2021
DOI: 10.1021/acsami.1c06089
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of a Metal–Organic Framework–Polymer Composite and Its CO2 Adsorption Performances from Humid Indoor Air

Abstract: Diamine-functionalized metal−organic frameworks (MOFs) are known as desirable adsorbents that can capture CO 2 even at low pressures, but the humidity instability of bare MOF powders as well as their shaping have not yet adequately addressed for practical applications. Herein, we report an effective synthetic strategy for fabricating millimeter-sized MOF/poly(vinylidene fluoride) (PVDF) composite beads with different amounts of PVDF binders (30, 40, and 50 wt %) via a phase inversion method, followed by the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Park et al [152] shaped diamine-functionalized epn-Mg 2 (dobpdc) MOF (dobpdc = 4,4′dioxido-3,3′-biphenyldicarboxylate, epn = 1-ethylpropane-1,3-diamine) into beads using poly(vinylidene fluoride) (PVDF). For this, the pristine MOF powder was dispersed in a DMF solution containing the polymer dissolved.…”
mentioning
confidence: 99%
“…Park et al [152] shaped diamine-functionalized epn-Mg 2 (dobpdc) MOF (dobpdc = 4,4′dioxido-3,3′-biphenyldicarboxylate, epn = 1-ethylpropane-1,3-diamine) into beads using poly(vinylidene fluoride) (PVDF). For this, the pristine MOF powder was dispersed in a DMF solution containing the polymer dissolved.…”
mentioning
confidence: 99%
“…188 In addition, MOF spheres with diameters of 2-3 mm prepared using a hydrophobic polymer binder, PVDF (poly(vinylidene fluoride)), and functionalized with epn follow the same CO 2 insertion mechanism, showing one-month stability at 25 1C at 60% RH. 433 A deeper understanding of the unprecedented cooperative adsorption mechanism of mmen-M 2 (dobpdc) was first reported by McDonald et al 423 in 2015. The mechanisms of diamine-M 2 (dobpdc) materials such as the dmen-M 2 (dobpdc) series 434 and mmen-M 2 (dobpdc) series 435 were investigated using more advanced experimental and simulation tools such as van der Waals (vdW)-corrected density functional theory calculations, single-crystal X-ray diffraction experiments, and quantum chemical methods.…”
Section: Novel Amine-functionalized Adsorbentsmentioning
confidence: 93%
“…, pressure drop and handling during application. 248 Finally, it has been suggested that the current cost of MOFs makes their use in DAC prohibitively expensive. 173 Notably, however, Mosaic Materials are developing CO 2 capture and indoor air quality control technologies based upon the use of MOFs (Table 1).…”
Section: Direct Air Capture Process Technology; State Of the Art And ...mentioning
confidence: 99%
“…247 Furthermore, the stability of powders under humidity is an issue, although strategies related to preparing composites with hydrophobic binders are beginning to appear, which may also help address issues related to e.g., pressure drop and handling during application. 248 Finally, it has been suggested that the current cost of MOFs makes their use in DAC prohibitively expensive. 173 Notably, however, Mosaic Materials are developing CO 2 capture and indoor air quality control technologies based upon the use of MOFs (Table 1).…”
Section: The Development Of Established Sorption-based Direct Air Cap...mentioning
confidence: 99%